An inquiry on the affordability of legal services and the appropriateness of the regular courts for consumer redress in Nigeria - Usman, Dahiru Jafaru (Scientific Research Publishing, 2016)
The paper assessed the appropriateness of the regular courts for consumer redress in Nigeria in view of delays, and the cost of legal services before the ordinary courts.The paper adopted a phenomenological qualitative research approach in exploring the perspectives and experience of government officials and other private bodies involved in consumer protection and consumer redress.Twenty face-to-face interviews were conducted, transcribed and thematically analysed. The study found that legal services are not affordable to the consumers and that the ordinary courts are inappropriate for consumer dispute resolution.The research participants were limited to officials of consumer protection, products standard setting agencies, legal aid, academics, and heads of consumer organizations. The participants excluded the ordinary consumer of goods and services in the country. The study recommends the establishment of a cheap, simple and expeditious redress mechanism for redressing the widespread consumer injustice in the country. A wellfunded legal aid scheme to bridge the gap between the poor consumer and the justice system is equally suggested.This study is the first attempt at qualitatively exploring in-depth the appropriateness of the justice delivery system for consumer redress in Nigeria.